1993
DOI: 10.1002/jmv.1890390315
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of HTLV‐I/II infection in seronegative high‐risk individuals

Abstract: The frequency of human T-cell lymphotropic virus types I and II (HTLV-I/II) polymerase chain reaction (PCR) reactivity was studied in two groups of high-risk individuals in Amsterdam: hard drug users and heterosexual outpatients of the sexual transmitted diseases (STD) clinic. Both groups were seronegative as determined by enzyme-linked immunosorbent assay (ELISA), Western blot (WB), and radioimmuno-precipitation assay (RIPA). Detection of HTLV-I and HTLV-II in peripheral blood mononuclear cells (MNC) was perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2002
2002
2005
2005

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…In general, HTLV-1-infected individuals have antibodies to structural proteins of the virus. However, it has been reported that some virus carriers and individuals with HTLV-1-associated diseases do not have detectable antibodies to HTLV-1 structural proteins [10][11][12][13][14] . Most virus carriers remain asymptomatic during their life, and the cofactors required for disease progression are largely unknown.…”
mentioning
confidence: 99%
“…In general, HTLV-1-infected individuals have antibodies to structural proteins of the virus. However, it has been reported that some virus carriers and individuals with HTLV-1-associated diseases do not have detectable antibodies to HTLV-1 structural proteins [10][11][12][13][14] . Most virus carriers remain asymptomatic during their life, and the cofactors required for disease progression are largely unknown.…”
mentioning
confidence: 99%